Tribal theory in Native American literature : Dakota and Haudenosaunee writing and indigenous worldviews - Kelsey, Penelope Myrtle (University of Nebraska Press, 2008)
This book raises the provocative issue of how Native languages and knowledges were historically excluded from the study of Native American literature and how their encoding in early Native American texts destabilized colonial processes. Cogently argued and well-researched, Tribal Theory in Native American Literature sets an agenda for indigenous literary criticism and invites scholars to confront the worlds behind the literatures that they analyze.